Cc2d1b Contributes to the Regulation of Developmental Myelination in the Central Nervous System - Acheta, Jenica; Hong, Jiayue; Jeanette, Haley; Brar, Simrandeep; Yalamanchili, Anish; Feltri, M. Laura; Manzini, M. Chiara; Belin, Sophie; Poitelon, Yannick (Frontiers in Molecular Neuroscience, 2022)
Background Numerous studies have indicated that myelination is the result of the interplay between extracellular signals and an intricate network of transcription factors. Yet, the identification and characterization of the full repertoire of transcription factors that modulate myelination are still incomplete. CC2D1B is a member of the Lgd/CC2D1 family of proteins highly expressed in myelinating cells in the central and peripheral nervous systems. In addition, the absence of CC2D1B limits myelin formation in vitro. Here we propose to delineate the function of CC2D1B in myelinating cells during developmental myelination in vivo in the central and peripheral nervous systems. Methods We used a Cc2d1b constitutive knockout mouse model and then performed morphological analyses on semithin sections of sciatic nerves and electron micrographs of optic nerves. We also performed immunohistological studies on coronal brain sections. All analyses were performed at 30 days of age. Results In the peripheral nervous system, animals ablated for Cc2d1b did not show any myelin thickness difference compared to control animals. In the central nervous system, immunohistological studies did not show any difference in the number of oligodendrocytes or the level of myelin proteins in the cortex, corpus callosum, and striatum. However, optic nerves showed a hypomyelination (0.844 ± 0.022) compared to control animals (0.832 ± 0.016) of large diameter myelinated fibers. Conclusions We found that CC2D1B plays a role in developmental myelination in the central nervous system. These results suggest that CC2D1B could contribute to gene regulation during oligodendrocytes myelination in optic nerves.